Entropy generation in MHD radiative viscous nanofluid flow over a porous wedge using the bivariate spectral quasi-linearization method. (September 2018) - Goqo, S.P.; Oloniiju, S.D.; Mondal, H.; Sibanda, P.; Motsa, S.S.
Abstract: We study the viscous nanofluid flow over a non-isothermal wedge with thermal radiation. The entropy due to irreversible processes in the system may degrade the performance of the thermodynamic system. Studying entropy generation in the flow over a porous wedge gives insights into how the system is affected by irreversible processes, and indicate which thermo–physical parameters contribute most to entropy generation in the system. The bivariate spectral quasi-linearization method is used to find the convergent solutions of the model equations. The impact of significant parameters such as the Hartmann number, thermophoresis and Brownian motion parameter on the fluid properties is evaluated and discussed. The Nusselt number, skin friction coefficients and Sherwood number are determined. An analysis of the rate of entropy generation in the flow for various parameters is presented, and among other results, we found that the Reynolds number and thermal radiation contribute significantly to entropy generation.